The Effects of Financial Literacy, Digital Payment, Business Experience, and Financial Inclusion on the Performance of Micro-Sub Sector MSMEs in Malang City (A Study of MSMEs Fostered by Rumah BUMN) - Benidektus Ragil Wahyu Dimas Prasetyo; Iwan Triyuwono (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The objective of quantitative descriptive this research is to identify the effects of financial literacy, digital payment, business experience, and financial inclusion on the performance of micro-sub sector MSME in Malang. The descriptive approach was used as this study elucidates the variables examined from certain phenomena by interpreting figures. From the population of 3,560 micro-sub sector MSMEs fostered by Rumah BUMN, 97 were selected as the samples via non-probability sampling method and purposive sampling technique. The research instruments have been tested for validity and reliability, and the acquired data have been assessed through classical assumption test and multiple linear regression; all statistical processes were performer in SPSS version 25.0. This study finds that financial literacy, digital payment, experience, and financial inclusion have positive and significant impacts on the performance of micro-sub sector MSMEs in Malang. This finding highlights the importance of financial literacy improvement and payment technology adoption in MSME performance enhancements and the cruciality of financial institutions’ support to boost MSME’s financial inclusion.